The Role of Artificial Intelligence in Credit Risk Management - Sonia Jindal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Artificial intelligence (AI) is rapidly transforming the financial services industry, and credit risk management is one area where AI is having a significant impact. AI-powered models can be used to analyze vast amounts of data to identify patterns and trends that may not be apparent to human analysts. This paper will discuss how AI is being used to improve credit risk assessment, fraud detection, and loan portfolio management. It will also explore the potential challenges and risks associated with using AI in credit risk management.